1982
DOI: 10.1021/i200016a033
|View full text |Cite
|
Sign up to set email alerts
|

Dilution of catalyst in a fluidized bed. Dehydration of ethanol

Abstract: I 5 6 7 3 9 1 0 1 1 !2 Catalyst loaalng x 10' 4 gm mi-' Figure 3. Effect of catalyst loading on reaction rate. expression (Table 111). A few experiments were also done varying the initial concentration of o-nitroaniline and the values of the specific reaction rate were observed to be essentially constant. Thus it appears that the kinetic data could be correlated by an empirical rate expression: r = Effect of Temperature. The temperature of the reaction was varied from 47 to 74 "C. The rate of the reaction incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The strategy of dilution by solids has been studied to improve packed-bed reactor performance and is now being increasingly applied. , The cost of catalyst forms a major component in reactor operation, and dilution can help in this aspect. In addition to packed-bed catalytic reactors, catalyst dilution by solids has been applied to fluidized-bed reactors , and trickle-bed reactors. , Care should be taken, however, to prevent bypass of flow inside a reactor while employing the dilution strategy. Catalyst dilution studies reported in the literature use inert solid−catalyst mixtures. In the present study, we assume that the catalyst is diluted with an adsorbent that acts not only as a diluent for the catalyst but also at the same time as an adsorbent for CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of dilution by solids has been studied to improve packed-bed reactor performance and is now being increasingly applied. , The cost of catalyst forms a major component in reactor operation, and dilution can help in this aspect. In addition to packed-bed catalytic reactors, catalyst dilution by solids has been applied to fluidized-bed reactors , and trickle-bed reactors. , Care should be taken, however, to prevent bypass of flow inside a reactor while employing the dilution strategy. Catalyst dilution studies reported in the literature use inert solid−catalyst mixtures. In the present study, we assume that the catalyst is diluted with an adsorbent that acts not only as a diluent for the catalyst but also at the same time as an adsorbent for CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][28][29][30][31] The cost of catalyst forms a major component in reactor operation, and dilution can help in this aspect. In addition to packed-bed catalytic reactors, catalyst dilution by solids has been applied to fluidized-bed reactors 32,33 and tricklebed reactors. 34,35 Care should be taken, however, to prevent bypass of flow inside a reactor while employing the dilution strategy.…”
Section: Introductionmentioning
confidence: 99%